MASALAH DAN TANTANGAN PENGEMBANGAN KEWIRAUSAHAAN PADA KALANGAN MAHASISWA DI INDONESIA - Imam Santosa (UII, 2014)
Indonesian nation face some important and crucial problem about poverty. One of which’s to overcome the amount of unemployment. It’s still relatively high plus the total labor force continues to grow each year. One thing is needed that number of entrepreneurs should be raised. Because of it as one of the indicators of economic progress. A number of obstacles facing, such as: social and economic constraints and market structure have not yet accomodate for conducting this. However, with improving education policy, curriculum and learning systems (students and lecturers relations) that can foster the emergence of a stimulus for innovation and creativity is convinced that these obstacles can be overcome. Keywords: SMEs, pooled data, fixed effect